Policy Professionals in Denmark - Poulsen, Birgitte; Aagaard, Peter (Politica, 2020)
The article examines whether we can detect the phenomenon policy professionals among employees in Danish interest organizations. In the theoretical part of the article, we clarify the concept of policy professionals. The empirical part is explorative and consists primarily of qualitative interviews. We conclude that policy professional is a relevant concept, when the aim is to understand the distribution and exercise of power in Denmark.